A Prospective Pilot Randomized Study: Electroacupuncture vs. Sham Procedure for the Treatment of Fatigue in Patients With Quiescent Inflammatory Bowel Disease. Issue 3 (15th May 2019) - Horta, Diana; Lira, Alba; Sanchez-Lloansi, Meritxell; Villoria, Albert; Teggiachi, Marcelo; García-Rojo, Dario; García-Molina, Susana; Figuerola, Ariadna; Esteve, Maria; Calvet, Xavier
Abstract: Background: Fatigue is a common symptom in patients with inflammatory bowel disease (IBD), and it often persists despite clinical remission. Acupuncture has been shown to be effective for treating fatigue in patients with many chronic diseases. The main objective of the study was to assess the efficacy of electroacupuncture (EAc), compared with sham EAc (ShEAc) or being on a waitlist (WL), for treating fatigue in patients with quiescent IBD in a single-blind randomized trial. Methods: Fifty-two patients with IBD in clinical remission and fatigue were randomly assigned to 1 of 3 groups: EAc, ShEAc, or WL. Patients in the EAc and ShEAc groups received 9 sessions over 8 weeks. Fatigue was evaluated with the IBD-validated Functional Assessment of Chronic Illness Therapy-Fatigue Scale (FACIT-FS). Results: Baseline characteristics were similar in the 3 groups. Both EAc and ShEAc presented improved Functional Assessment of Chronic Illness Therapy-Fatigue Scale scores compared with baseline: the respective improvements were 9.53 (95% confidence intervals, 6.75–12.3, P < 0.001) and 5.46 points (95% confidence intervals, 2.7–9.7, P = 0.015), respectively. No significant changes were observed in the WL group. In the comparison of treatment groups, EAc was nonsignificantly better than ShEAc (EAc, 33.27 and ShEAc, 28.13, P = 0.168); both EAc and ShEAc improved fatigue scores significantly compared to WL (24.5; P = 0.01 and 0.04, respectively). Conclusions: Both EAc and ShEAc reduced fatigue scores in IBD patients when compared to WL. No differences were observed between EAc and ShEAc, although the study was not powered to rule out a difference. Acupuncture may offer improvements to patients with few other treatment alternatives. Clinical Trials Org Id: NCT02733276. Abstract : Fatigue is common in patients with inflammatory bowel disease (IBD), and it often persists despite clinical remission. There are no efficacious therapies for the management of fatigue in patients with IBD. We aimed to evaluate the efficacy of electroacupuncture in patients with quiescent IBD.